THE USE OF DRILLING TECHNIQUES INTEGRATED WITH TECHNOLOGY TO IMPROVE STUDENT'S VOCABULARY MASTERY AT SD NEGERI 4 KALIUNTU - Pratiwi, Ketut Rona; Dewi, Kadek Sintya; Mahendrayana, Gede (Universitas Suryakancana, 2025)
This study aims to improve student's vocabulary mastery by using drilling techniques integrated with technology in students of SD Negeri 4 Kaliuntu. This study used Classroom Action Research (CAR). Fourth-grade elementary school students were the subject of this study, with a total of 34 students. The data was obtained using a vocabulary test (pre-test and post-test), which was conducted through two cycles of planning, action, observation, and reflection. The findings showed that the use of drilling techniques integrated with technology through vocabulary video can improve students' vocabulary mastery. It was indicated by the data obtained on the students' vocabulary test, namely in the first cycle student’s who passed the Minimum Mastery Criteria of 70 was 82.35% with the difference from the pre-test to the first cycle post-test was 31.07%. A drastic significant increase occurred in the second cycle with students passing the Minimum Mastery Criteria of 70 was 100%. In addition, the improvement of students' vocabulary mastery also changed through students' opinions about the use of drilling techniques integrated with technology has a significant impact on student's vocabulary mastery.